ANALYSIS OF IMAGE INFORMATION WHEN EMPLOYING THE DIFFUSION WEIGHTED IMAGING (DWI) SEQUENCES WITH ‘B’ VALUE VARIATION FOR INTRACRANIAL TUMOR CASE - Maizza Nadia Putri; Lydia Purna W.S.K; Siti Masrochah (Politeknik Kesehatan Kementerian Kesehatan Semarang, 2022)
Background: One variation of pulse sequence used in MRI Brain examination is Diffusion Weighted Image (DWI). In the DWI sequence, the value of 'b' which the operator must choose when setting the parameters, affects the signal intensity. In radiology installations, radiographers often use a 'b' value of 1000 s/mm2 with various pathologies. The purpose of this study was to determine the effect of setting the value of 'b' (1000.1500.2000 s/mm2) on image information and to determine the best setting of the three selected 'b' values in generating DWI signals for cases of intracranial tumors.Methods: This research is experimental study. This research uses MR GE 1.5 Tesla. 6 radiographic images were created with three 'b' value settings. Three radiologists then assessed areas of white matter, gray matter, proc. coronoid, basal ganglia and tumor lesions. The results were then analyzed using the Friedman statistical test.Results: The results showed that there were differences in signal intensity and image quality between the three setting values of 'b' with p value 0.005. The mean rank indicates that the best setting 'b' value in producing high signal intensity in Basal ganglia, Proc. coronoid and tumor lesions is 1500 s/mm2 (Mean rank: 2.75 and 2.42). then for white matter and gray matter the best 'b' value setting is 1000 s/mm2 (average rating: 2.50).Conclusion: There is a significant difference in MRI Brain image information with variations in the